Age and gender interactions in short distance triathlon performance - Etter, F.; Knechtle, B.; Bukowski, A.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Journal of Sports Sciences, 2013)
This study investigated the participation and performance trends as well as the age and gender interaction at the Olympic distance `Zürich Triathlon` (1.5 km swim, 40 km cycle and 10 km run) from 2000 to 2010 in 7,939 total finishers (1,666 females and 6,273 males). Female triathletes aged from 40 to 54 years significantly (P?<?0.05) increased their participation while the participation of younger females and males remained stable. Males of 50-54 years of age and females of 45-49 years of age improved their total race time. For elite top five overall triathletes, mean gender differences in swimming, cycling, running and overall race time were 15.2?±?4.6%, 13.4?±?2.3%, 17.1?±?2.5%, and 14.8?±?1.8%, respectively. For both elite and age group athletes, the gender difference in cycling time was significantly (P<0.001) lower than for swimming and running. The gender difference in overall Olympic distance triathlon performance increased after the age of 35 years, which appeared earlier compared to long distance triathlon as suggested by previous studies. Future investigations should compare gender difference in performance for different endurance events across age to confirm a possible effect of exercise duration on gender difference with advancing age.